Analysis of the Thermal Effects on the Behaviour of Steel Connection Beam Section - Seelam Srikanth; Sai Nitesh KJN; Chunchu Bala Rama Krishna; Vasugi K; Cheerla Prabhu Teja; Sesha Rao Y; Sanjeev Kumar; Dumesa Gudissa Lemu (Advances in Materials Science and Engineering)
Steel connection is utilized to link the beam and column. It moves the plastic hinge structure away at a predetermined distance from the face of the column. To lower the cross-sectional area of the beam flanges, several shape cuts (uniform, radius, taper, and straight cut) are available, and a piece of the beam flanges at the column face is purposefully intended to yield and plastic hinge. The use of a lowered beam section connection reduces stress absorption since the criteria for a strong column–weak beam are met. The ANSYS 14.5 software was used to model four types of reduced beam sections by decreasing the beam flange. In various patterns, fatigue behaviour was studied. The objective of this project is to evaluate the deformations, stresses and transient temperatures deformations, and stresses of the reduced beam section at static structural analysis. In comparison to other connections, steel connection reduced beam section ductile and dissipated energy more. A nonlinear finite element software was used, along with a static study of exhaustion responsiveness transient temperatures. The analysis is carried out to identify the thermal effects on the behaviour of material properties in the elastic and plastic regions. The members with cuts have performed superior in comparison with members without cuts.